Rental relations in maritime economic activities - Parsyak, V. N.; Solesvik, M. B. (My University, 2017)
Based on the views of predecessors, the authors have examined the essence of rent and rental relations as essential economic and legal categories. The growth of their importance in the rapid development of the world’s maritime economy is highlighted, as is the exhaustion of natural resources that ensure human life and activities. The negative consequences of the authorities’ irresponsibility towards the improvement of rental relations are outlined.
Parsyak, V. N. Rental relations in maritime economic activities / V. N. Parsyak, M. B. Solesvik // Shipbuilding & Marine Infrastructure. – 2017. – № 2 (8). – P. 152–165.
Keywords: maritime economy; rent; rental relations; rental income; rental payment; type of rent; rental rate